Temporal shifts of nitrite reducing communities in a rice field soil in Ibague (Colombia) (2016)
Denitrification and nitrification are microbial processes that regulate the cycle of nitrogen and nitrous oxide, which is considered an important greenhouse gas. Rice field soils have been known to have strong denitrifying activities; however, the microorganism structure that is responsible for denitrification and the temporal variation of these communities in the agricultural soils of Ibague (Colombia) is not well known. In this study, the denitrifying community composition was compared between a rice field soil and an uncultivated soil at three different times during the year using a terminal restriction fragment length polymorphism analysis of the nirS functional gene, which codes the enzyme that reduces nitrite, one of the key steps in the denitrification process. The results showed changes in the richness, relative abundance and diversity of the operational taxonomic units between the soils and sampling times. The canonical correspondence analysis indicated that the moisture and the pH were the environmental factors that explained the observed changes in the nirS-type denitrifiers' community composition in the studied soils.